Tailoring Nanomaterials for Targeting Tumor‐Associated Macrophages. Issue 19 (18th March 2019) - Ovais, Muhammad; Guo, Mengyu; Chen, Chunying
Abstract: Advances in the field of nanotechnology together with an increase understanding of tumor immunology have paved the way for the development of more personalized cancer immuno‐nanomedicines. Nanovehicles, due to their specific physicochemical properties, are emerging as key translational moieties in tackling tumor‐promoting, M2‐like tumor‐associated macrophages (TAMs). Cancer immuno‐nanomedicines target TAMs primarily by blocking M2‐like TAM survival or affecting their signaling cascades, restricting macrophage recruitment to tumors and re‐educating tumor‐promoting M2‐like TAMs to the tumoricidal, M1‐like phenotype. Here, the TAM effector mechanisms and strategies for targeting TAMs are summarized, followed by a focus on the mechanistic considerations in the development of novel immuno‐nanomedicines. Furthermore, imaging TAMs with nanoparticles so as to forecast a patient's clinical outcome, describing treatment options, and observing therapy responses is also discussed. At present, strategies that target TAMs are being investigated not only at the basic research level but also in early clinical trials. The significance of TAM‐targeting biomaterials is highlighted, with the goal of facilitating future clinical translation. Abstract : Novel approaches for designing nano‐materials for tumor‐associated macro‐phages (TAMs) targeting and advances in imaging TAMs via nanoparticles are summarized. The nano–bio interface for targeting various TAM signaling pathways, leading to inhibition of recruitment, interference with survival, and re‐education, is of potential clinical significance. The interface of TAMs, nanomedicine, and imaging can be a promising step for cancer immuno‐nanomedicines development.